A methods engineering study on FVT Corporation - De Leon, Irene; Villarin, Andrea; Villegas, Camilla (Diliman, Quezon City College of Engineering, 1999)
This paper is a documentation of a work study conducted on FVT Corporation, a manufacturing company engaged in customizing metal products for telecommunication and banking use. Its product line includes steel racks, cabinets, tables, consoles and other metal products used in offices and industries. A job shop by nature, the company operates depending on its clients' desired specifications. This study illustrates that the lack of standardization creates problems in methods and consequently, in productivity is affected as well. The company under study considers production delay as its major problem area. A methods study is conducted to identify the factors affecting production delay and to propose improvements in the current production process. A time study is done in order to come up with a standardized time. With the findings of the work study, the reserchers hope to contribute towards improving the production system of the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Manufacturing industries; Systems analysis